2011
DOI: 10.14742/ajet.983
|View full text |Cite
|
Sign up to set email alerts
|

Using video annotation to reflect on and evaluate physical education pre-service teaching practice

Abstract: This case study examined the integration of a media annotation tool (MAT) into the learning and assessment activities of an undergraduate teaching (physical education) course. The media form or artefact for annotation was video recordings demonstrating individual learners' teaching practice. The learners categorised (marked sections) and annotated their videos and received peer and teacher feedback within the tool. Their use of MAT was analysed to determine if this learning environment was effective in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 28 publications
0
69
0
4
Order By: Relevance
“…Twenty-one articles reasoned from social constructivism: Licklider (1995), Black and Wiliam (1998), Tillema and Smith (2000), MacDonald (2001), Manouchehri (2002), Mory (2003), Schelfhout, Dochy, and Janssens (2004), Gibbs and Simpson (2004), Yang and Liu (2004), Weaver (2006), Hattie and Timperley (2007), Brandt (2008), Segers, Gijbels, and Thurlings (2008), Landry, Anthony, Swank, andMonseque-Bailey (2009), Fund (2010), Gielen, Peeters, Dochy, Onghena, and Struyven (2010), Kretlow and Bartholomew (2010), Li, Liu, and Steckelberg (2010), Martens, de Brabander, Rozendaal, Boekaerts, and Van der Leeden (2010), Colasante (2011), and Van der Kleij, Eggen, Timmers, and Veldkamp (2012).…”
Section: Data-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-one articles reasoned from social constructivism: Licklider (1995), Black and Wiliam (1998), Tillema and Smith (2000), MacDonald (2001), Manouchehri (2002), Mory (2003), Schelfhout, Dochy, and Janssens (2004), Gibbs and Simpson (2004), Yang and Liu (2004), Weaver (2006), Hattie and Timperley (2007), Brandt (2008), Segers, Gijbels, and Thurlings (2008), Landry, Anthony, Swank, andMonseque-Bailey (2009), Fund (2010), Gielen, Peeters, Dochy, Onghena, and Struyven (2010), Kretlow and Bartholomew (2010), Li, Liu, and Steckelberg (2010), Martens, de Brabander, Rozendaal, Boekaerts, and Van der Leeden (2010), Colasante (2011), and Van der Kleij, Eggen, Timmers, and Veldkamp (2012).…”
Section: Data-analysismentioning
confidence: 99%
“…From social cultural theory, feedback can help to identify and correct errors and can explain misunderstandings (Orsmond & Merry, 2011). Articles from behaviourism (e.g., Auld et al, 2010;Goodman et al, 2008), cognitivism (e.g., Shute, 2008), social cultural theory (Ackan & Tatar, 2010;Brinko, 1993;Yeh & Lo, 2009) and social constructivism (Colasante, 2011;Gielen et al, 2010) indicated that feedback should be specific and clear. Others used different terms: feedback should be concrete (Brinko, 1993) consistent (Brinko, 1993;Ovando, 2005; from social cultural theory), and descriptive (Fund, 2010;Kretlow & Bartholomew, 2010; from social constructivism).…”
Section: Characteristics Of Effective Feedback and Learning Theoriesmentioning
confidence: 99%
See 3 more Smart Citations